2013
DOI: 10.1364/oe.21.030947
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantitative analysis of 3D morphology and mean corpuscular hemoglobin in human red blood cells stored in different periods

Abstract: Quantitative phase (QP) images of red blood cells (RBCs), which are obtained by off-axis digital holographic microscopy, can provide quantitative information about three-dimensional (3D) morphology of human RBCs and the characteristic properties such as mean corpuscular hemoglobin (MCH) and MCH surface density (MCHSD). In this paper, we investigate modifications of the 3D morphology and MCH in RBCs induced by the period of storage time for the purpose of classification of RBCs with different periods of storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…[13][14][15][16] Many efforts have been made in RBC studies to detect abnormalities in samples before transfusion to the patient to prevent future disorders caused by the malfunction of RBCs. [17][18][19] According to the above discussion, we believe the utilization of clustering techniques can provide us with reasonable results. Therefore, because of the irregularly shaped groups of RBC types distributed in feature space, the density-based clustering method can be effective in this case and for overlapped RBC data.…”
Section: Introductionmentioning
confidence: 89%
“…[13][14][15][16] Many efforts have been made in RBC studies to detect abnormalities in samples before transfusion to the patient to prevent future disorders caused by the malfunction of RBCs. [17][18][19] According to the above discussion, we believe the utilization of clustering techniques can provide us with reasonable results. Therefore, because of the irregularly shaped groups of RBC types distributed in feature space, the density-based clustering method can be effective in this case and for overlapped RBC data.…”
Section: Introductionmentioning
confidence: 89%
“…More recently, more detailed RBC analyses came into the game and have pictured out other storage lesions (see Table 1). These studies reported the presence of reversible [18,[27][28][29][30][31] and irreversible modifications [19,[23][24][25][26]32,33] during aging. Moreover, and especially since the 2008 Koch's paper [1], several authors have tried to define a storage limit other than the expiration date.…”
Section: Ec Age Based On In Vitro Assaysmentioning
confidence: 99%
“…Current protocols call for the destruction of these stored blood components after 42 days, based on guidelines from the Committee for Standardization in Haematology [15]. As RBCs age, they lose the important flexibility and deformability that enables them to squeeze through small capillaries to deliver oxygen to tissue; this capability cannot be regained after the transfusion occurs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous optical imaging studies of RBC morphology have required breaching the storage bag; these efforts, like those described above, found irreversible changes to the morphology with increasing storage duration [13][14][15]. Nonlinear optical imaging of RBCs has been accomplished via several different methods including two-photon absorption (TPA) [2,16], TPEF [3,17], and THG [18,19].…”
Section: Introductionmentioning
confidence: 99%